System responsiveness of antioxidant chelators in employees in dynamics of chronic exposure to industrial toxicants - I. V. Kudayeva; L. B. Masnavieva; L. A. Budarina (Acta Biomedica Scientifica, 2013)
Purpose: to study the content changes of the antioxidants-chelators in dynamics of examining the persons exposed to the toxic substances. The cohort examination (with the interval of 4 years) of the employees exposed to the metallic mercury vapours, vinyl chloride (VC) and epichlorohydrin (EPCH) has been performed. All the employees were divided into groups in dependence on the working period at the moment of the first examination. The content of ceruloplasmin (CP), the uric acid (UA) and the activity of superoxide dismutase (SOD) in the blood have been studied. Statistical processing the results was performed using the packet of applied programs "Statistica 6.0". The compensatory mechanisms of the responses were found to be different for the antioxidants-chelators in exposure to mercury and chlorine-bearing compounds. The exposure to mercury may promote the increase in the level of CP at the background of the decrease in the activity of SOD and have the stable character in time after 5 years of work and exposure to toxicant. In exposure to VC the analogous compensatory changes were found to begin after 10 years of production working careere and keep for the following 5 years of work. The further exposure to this toxicant may lead to the de-compensatory changes in the system of SOD-CP. The chronic exposure to EPCH may be followed by the increase in the level of UA, acquiring the pathogenetic character in 25 % of persons worked more than 10 years and the increase in the activity of SOD for the working period more than 15 years. The findings allow to conclude about the necessity of performing the timely preventive measures for the persons above. However, the trend and the time period of their initiation may be different. In the case of exposure to mercury the necessity of using the antioxidants (ascorbic acid, unsaturated fatty acids) may arise already after 5years of exposure to the toxicant. In exposure to vinyl chloride the analogous measures have to begin after 10 years of work. There to, using vitamin C is considered as purposeless. On the contrary, the preventive use of this antioxidant, beginning from 10 years of the production working period, is indicated for the employees exposed to epichlorohydrin.